CRITICISMS TOWARD JAVANESE CULTURE IN PRAMOEDYA ANANTA TOER'S BUMl MANUSlA: AN ANALYSIS ON THE DOMINANT CULTURE OF THE PRIYAYI - Yohanes Hartadi (Soegijapranata Catholic University, 2001)
It is not an exaggeration if we say Java-with its people and its culture-Dominates almost all aspects of the Republic of Indonesia. Many Javanese things are used and imitated by people other than Javanese. Pramoedya Ananta Toer. as a Javanese writer. sees the Javanese culture from another angle. He is able to notice the inappropriate Javanese concepts and prac.tices. Bumi Manusia is a novel that reveals Pramoedya's criticisms toward Javanese culture